Longitudinal assessment of PCBs and chlorinated pesticides in pregnant women from Western Canada - Hauser Russ; Chan Siu; Jarrell John; Hu Howard (BMC, 2005)
Abstract Background Maternal exposures to organochlorines prior to pregnancy are considered a risk to neonatal welfare, specifically in relation to neurocognitive functions. There is growing interest in the evaluation of maternal blood testing as a marker for fetal exposure as well as the variable geographic distribution of these priority chemicals. Methods Three hundred and twenty-three women in the second trimester of pregnancy entered the study at a prenatal clinic providing genetic counselling information. Subjects who had an indication for genetic amniocentesis based on late maternal age were eligible to participate. Two hundred and thirty-eight completed an environmental questionnaire. A sample of amniotic fluid was taken for karyotype analysis in 323 women and blood samples during pregnancy (209), at birth (105) and from the umbilical cord (97) and breast milk (47) were also collected. These samples were tested for 29 PCB congeners and organochlorine pesticides. Results The concentrations of PCB 153 in these media were relatively low in relation to other studies. Σ PCBs measurements in samples taken during the second trimester of pregnancy, at birth and in the umbilical cord were strongly correlated. Specific measurements of PCB 153 and PCB 180 among those subjects with completed sampling of blood samples from mothers and cord samples were significantly correlated. The concentrations of PCBs and pesticides did not differ in relation to prior spontaneous abortion history. There were no organochlorines present in the amniotic fluid at the current level of quantification. Conclusion Pregnant women from the Western Canada region of Calgary, Alberta are exposed to relatively low concentrations of organochlorines. Measurement of maternal blood during the second trimester of pregnancy can reliably estimate the fetal exposure to PCBs. This estimate is reliable for Group 2 and 3 PCBs as well as PCB 153 and PCB 180. The amniotic fluid does not contain measurable concentrations of pesticides and PCBs under the conditions of the levels of quantification.